Fungal Planet description sheets: 1550–1613 - Crous, P.W. (Pedro Willem); Costa, M.M.; Kandemir, H.; Vermaas, M.; Vu, D.; Zhao, L.; Arumugam, E.; Flakus, A.; Jurjević, Ž.; Kaliyaperumal, M.; Mahadevakumar, S.; Murugadoss, R.; et al. (Persoonia - Molecular Phylogeny and Evolution of Fungi, 2023)
Novel species of fungi described in this study include those from various countries as follows: Argentina, Neocamarosporium halophilum in leaf spots of Atriplex undulata. Australia, Aschersonia merianiae on scale insect (Coccoidea), Curvularia huamulaniae isolated from air, Hevansia mainiae on dead spider, Ophiocordyceps poecilometigena on Poecilometis sp. Bolivia, Lecanora menthoides on sandstone, in open semi-desert montane areas, Sticta monlueckiorum corticolous in a forest, Trichonectria epimegalosporae on apothecia of corticolous Megalospora sulphurata var. sulphurata, Trichonectria puncteliae on the thallus of Punctelia borreri. Brazil, Catenomargarita pseudocercosporicola (incl. Catenomargarita gen. nov.) hyperparasitic on Pseudocercospora fijiensis on leaves of Musa acuminata, Tulasnella restingae on protocorms and roots of Epidendrum fulgens. Bulgaria, Anthracoidea umbrosae on Carex spp. Croatia, Hymenoscyphus radicis from surface-sterilised, asymptomatic roots of Microthlaspi erraticum, Orbilia multiserpentina on wood of decorticated branches of Quercus pubescens. France, Calosporella punctatispora on dead corticated twigs of Acer opalus. French West Indies (Martinique), Eutypella lechatii on dead corticated palm stem. Germany, Arrhenia alcalinophila on loamy soil. Iceland, Cistella blauvikensis on dead grass (Poaceae). India, Fulvifomes maritimus on living Peltophorum pterocarpum, Fulvifomes natarajanii on dead wood of Prosopis juliflora, Fulvifomes subazonatus on trunk of Azadirachta indica, Macrolepiota bharadwajii on moist soil near the forest, Narcissea delicata on decaying elephant dung, Paramyrothecium indicum on living leaves of Hibiscus hispidissimus, Trichoglossum syamviswanathii on moist soil near the base of a bamboo plantation. Iran, Vacuiphoma astragalicola from stem canker of Astragalus sarcocolla. Malaysia, Neoeriomycopsis fissistigmae (incl. Neoeriomycopsidaceae fam. nov.) on leaf spots on flower Fissistigma sp. Namibia, Exophiala lichenicola lichenicolous on Acarospora cf. ...